MODELLING A CONCEPTUAL FRAMEWORK OF TECHNOLOGY TRANSFER PROCESS IN CONSTRUCTION PROJECTS: AN EMPIRICAL APPROACH - De-Graft OWUSU-MANU; Erika Anneli PÄRN; Maxwell Fordjour ANTWI-AFARI; David John EDWARDS (Journal of Construction Project Management and Innovation)
Technology transfer (TT) is crucial to social infrastructure and economic development in developing countries (DCs). In Ghana’s construction sector, foreign firms provide an invaluable source of innovation and technological advancement for local contractors. However, TT models published in existing literature are rarely applicable to the construction industry in DCs. This paper therefore presents a conceptual framework of the TT process as a tool for measuring construction performance. Utilising the results from a questionnaire survey of Ghanaian construction industry professionals, eight different perspectives on TT were formulated using exploratory factor analysis. These perspectives represent the enablers and outcomes of the TT process, namely transferor and transferee characteristics, knowledge advancement, the transfer environment, government influence, the learning environment, project performance, communication, and relationship building and absorptive capability. The research outcomes provide useful guidance to local and international funding agencies, governments of developing or newly industrialised countries, and construction firms that seek to effectively evaluate the success (or otherwise) of the TT process. Future research should seek to validate the research findings presented, and to expand the work to include other DCs.